Decreased CCL5 expression in endometrial stromal cells induces deficient CCR5+CD4+ T cells in endometriosis - Li Yue; Li Yunyun; Lu Yewei; Lin Yikong; Wang Xiaolin; Zhu Yizhun; Zeng Qiongjing; Du Meirong (Acta Biochimica et Biophysica Sinica)
Endometriosis (EMS) is a benign gynecological disease characterized by the growth of endometrial tissue outside the uterine cavity. Evidence shows that the survival of patients with ectopic endometrial implants is associated with a dysregulated immune microenvironment. CD4+ T cells can regulate EMS through diverse cytokines, the inflammatory response, and angiogenesis. CCR5+CD4+ T cells exhibit increased cellular immunogenicity and play a role in infectious diseases, host defense, and cancer progression. However, the specific mechanisms of CCR5+CD4+ T cells in EMS remain unknown. In the present study, flow cytometry and RNA-seq are utilized to assess the proportions and features of CCR5+CD4+ T cells in EMS patients, RT-PCR and ELISA are used to assess the production of CCL5 by ectopic endometrial stromal cells (ecESCs). Two EMS models are established through C57B6 wild-type and CCL5‒/‒ mice and utilized to explore the in vivo effects of CCR5+CD4+ T cells on ectopic lesions. Compared with CCR5‒CD4+ T cells, CCR5+CD4+ T cells display a more activated and cytotoxic phenotype. Diminished CCR5+CD4+ T cells and their impaired ability to produce IFN-γ are observed in the ectopic lesions of EMS patients and in murine EMS models. Impaired production of CCL5 has been detected in human ecESCs. Moreover, endometria stripped from CCL5‒/‒ mice are more likely to generate ectopic lesions in the peritoneum of recipient mice. These findings demonstrate that the attenuated recruitment of CCR5+CD4+ T cells in ectopic lesions caused by decreased production of CCL5 in ecESCs may facilitate the progression of EMS.